2016
DOI: 10.1007/s11897-016-0296-6
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 and Utility in Heart Failure: Just Another Supplement?

Abstract: Heart failure affects 5.1 million people in the USA annually. It accounts for a frequent cause of hospitalizations and disability. Patients with congestive heart failure have lower plasma levels of CoQ10, which is an independent predictor of mortality in this patient population. It has been hypothesized that a deficiency of CoQ10 can play a role in the development and worsening of heart failure, and that oral supplementation can possibly improve symptoms and survival in these patients. Based on previous small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
(51 reference statements)
0
23
1
1
Order By: Relevance
“…Levels of CoQ10 tend to decline with age, and deficiency has been associated with diseases such as HF. In fact, a close positive correlation between HF severity and severity of CoQ10 deficiency has been identified (Oleck & Ventura, 2016). It has been proposed that the antioxidant and free radical scavenging properties of CoQ10 are important in combatting harmful effects from the high ROS observed in HF patients (Sharma, Fonarow et al, 2016).…”
Section: Mitochondrial-targeted Antioxidantsmentioning
confidence: 98%
See 1 more Smart Citation
“…Levels of CoQ10 tend to decline with age, and deficiency has been associated with diseases such as HF. In fact, a close positive correlation between HF severity and severity of CoQ10 deficiency has been identified (Oleck & Ventura, 2016). It has been proposed that the antioxidant and free radical scavenging properties of CoQ10 are important in combatting harmful effects from the high ROS observed in HF patients (Sharma, Fonarow et al, 2016).…”
Section: Mitochondrial-targeted Antioxidantsmentioning
confidence: 98%
“…It has been proposed that the antioxidant and free radical scavenging properties of CoQ10 are important in combatting harmful effects from the high ROS observed in HF patients (Sharma, Fonarow et al, 2016). Furthermore, the vital role of CoQ10 in oxidative phosphorylation suggests that ATP generation may be directly enhanced via CoQ10 supplementation (Oleck & Ventura, 2016).…”
Section: Mitochondrial-targeted Antioxidantsmentioning
confidence: 99%
“…Reduced levels of CoQ10 in the aging and those with DM have been reported [18]. CoQ10 supplementation influences the cholinergic system and protects cholinergic neurons in patients with Alzheimer’s disease [19-21], as well as improving cardiovascular function [22]. In addition, CoQ10 can reduce hyperglycemia [23-25], thereby protecting against endothelial abnormalities and dysfunction in DM [24] and reducing oxidative stress [24, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with worsening symptoms and left ventricular dysfunction tend to have lower CoQ10 levels, and administration of CoQ10 seems to improve left ventricular function. 3 Finally, a systematic review recently demonstrated that in 3 randomized control trials, micronutrient repletion improved ejection fraction and quality of life in patients with heart failure. 4 This patient presented with new systolic heart failure and responded to repletion of various micronutrients and vitamins.…”
Section: Discussionmentioning
confidence: 99%